Aquisição e manutenção de comportamentos de leitura e fluência através de contingências de repetição oral e velocidade nos procedimentos de equivalência de estímulos. - Zuliani, Giovana (2007)
The studies described here are related to the acquisition of reading behaviors, and are based on the stimulus equivalence paradigm. The objectives of Study 1 had been to investigate if the incorporation of the repetition of an auditory stimulus, in a CRMTS procedure, would facilitate the acquisition of repertoires in dictated and would create reading behaviors. Also, to verify the effect of time intervals on the maintenance of repertoires acquired in trainings. Six participants had been trained in tasks of copy and dictated by construction of anagrams. The research software Mestre® was used throughout the study. In the copy task, after the presentation of a printed word, the experimenter emitted the name of the word and requested the repetition by the participant. In the dictated task, a word was dictated by the computer, and the participant had to repeat it. In these tasks, after the repetition, comparison stimuli were presented. Correct choices were followed by fiches and compliments. Incorrect choices produced the interval between attempts (IET). A set of 12 words was taught. In order to analyze the maintenance, three trained words were reserved and presented in the final test. As a result, the procedure favored the gradual acquisition of the dictated repertoire, as well as made the development of reading with understanding and receptive reading possible, and emergency of writing with understanding and expressive reading of trained and generalization words. During the final test, it was possible to observe standards of similar answers in the maintenance of the reserved words, in relation to the words tested immediately. The results had shown the acquisition of literal behaviors in relation to the words, and served as a base to the delineation of Study 2, which objective was to favor the acquisition and maintenance of reading of words and texts, in a fluent way. A version of the Mestre®, called Mestre2005 was used. An additional objective was to evaluate the maintenance of the repertoires, in relation to the accuracy and speed, 30, 60 and 90 days after the trainings. Trainings in MTS of receptive reading were presented. In this task, upon the word dictated by the computer, the participant was asked to repeat it, and after that, the comparison stimuli were presented. Correct choices produced an animation in the screen and compliments, and incorrect choices produced the IET of 1s. A set of three words was taught with accuracy criteria only. After criteria, the same three words were presented in the condition of accuracy and speed. In this condition, a contingency of time to the task of receptive reading was inserted. To each attempt, the latency was calculated automatically, favoring, thus, the modeling of fast answers, attempt by attempt. The criteria were correct and fast answers, therefore, fluent. A reading test was carried through, in which three texts with words of generalization and different levels of difficulty that had been presented before, during and after the trainings, and in the tests of maintenance of 30, 60 and 90 days. The objective was to measure the number of words correctly read per minute, in order to evaluate accuracy and fluency, and to verify if the procedure was effective to develop the reading of texts. The procedure of MTS combined with the speed was effective to develop behaviors of reading and fluency of words and texts, but only for the participants who possessed some repertoire of entrance. In this way, new inquiries on the incorporation of repetition and speed are suggested to favor the acquisition and maintenance of reading behaviors.